ENT 530 Social Media Portfolio / Siti Nur Farhana Mukhtar Affandi - Mukhtar Affandi, Siti Nur Farhana (2019)
Gelang.Hanz offers custom made bracelet accessories for customers, providing the variety design and colour of the bracelet that gives high satisfaction to customers.